One Health and antimicrobial resistance - Moodley, Arshnee (International Livestock Research Institute, 2021)
Arshnee Moodley, team leader of the CGIAR Antimicrobial Resistance Hub, explains what antimicrobials are, their importance in human health and why One Health is important in tackling antimicrobial resistance. This film is part of the ILRI and CGIAR 'Investing in One Health' video series.